Integrating E-learning into Medical Education – Phase-I of MBBS Programme in Bangladesh: Prospects and Challenges for the Students, Instructors and Policy Makers - Nurunnabi, Abu Sadat Mohammad; Mozaffor, Miliva; Tabassum, Mariya; Akhter, Qazi Farzana; Johora, Fatema (Community Based Medical Journal, 2024)
Over the past few decades, there has been a shift in medical education from the traditional didactic model of instruction to other modalities like online or electronic learning (e-learning). E-learning is being increasingly utilized in medical education across the globe through adaptive tutorials, audiovisual clips, simulation, and virtual models/atlas. This review aims to identify the prospects and challenges of integration of e-learning into Phase-I of MBBS Programme in Bangladesh and discuss solutions from medical educators’ perspectives. Elearning has been demonstrated to be as effective as conventional teaching and learning. It allows more personalized, self-directed learning experience for the medical students. Instructors can evaluate competencies objectively through online assessments, provide personalized feedback for self-improvement to the students. For policy makers, e-learning could hold the key to success in delivering quality medical education even in those medical colleges established in the remote semi-urban areas addressing the nation’s most entrenched medical teacher vacancies especially in basic subject areas like anatomy, physiology, and biochemistry. Challenges that affect the development and implementation of e-learning in medical education include lack of time and efforts, low technical skills, resource-poor infrastructure, lack of institutional strategies and support and stakeholders' negative attitude towards e-learning. Solutions to those problems may include training for professional development of the faculties with improvement of technical skills, incentives for the time and efforts in development and delivery of online content, favorable digital and tech-friendly institutional strategies and growing positive attitude towards online medical education, and above all, political commitment to ensure quality medical education. CBMJ 2024 July: vol. 13 no. 02 P: 290-297